1992
DOI: 10.1111/j.1365-2249.1992.tb02992.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis ofGiardia lambliatrophozoites by cytokine-activated macrophages

Abstract: SUMMARY Phagocytosis of Giardia lamblia trophozoites by cytokine‐activaled and non‐activated bone marrow‐derived macrophages was examined in vitro. Macrophages treated with recombinant interferon‐gamma (IFN‐γ) and bacterial lipopolysaccharide (LPS) ingested a significantly higher number of in vitro‐grown trophozoites than untreated macrophages. Maximal uptake of parasites occurred after 4 h and 6 h of incubation where 81.4% and 79.1% of macrophages were positive for trophozoites. Other cytokines tested, IL‐2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The increase of trophozoite levels in relation to cells (3:1) did not significantly influence trophozoite adherence and ingestion, in agreement with other research 24 in which a 10‐fold increase in the number of available trophozoites for interaction with macrophages did not alter the level of phagocytic activity. The percentage of dead intracellular trophozoites reached almost 50%, indicating that these phagocytes may have a double functional role as effector cells and also as antigen‐presenting cells.…”
Section: Discussionsupporting
confidence: 91%
“…The increase of trophozoite levels in relation to cells (3:1) did not significantly influence trophozoite adherence and ingestion, in agreement with other research 24 in which a 10‐fold increase in the number of available trophozoites for interaction with macrophages did not alter the level of phagocytic activity. The percentage of dead intracellular trophozoites reached almost 50%, indicating that these phagocytes may have a double functional role as effector cells and also as antigen‐presenting cells.…”
Section: Discussionsupporting
confidence: 91%
“…The activation of immune factors, such as T cells, neutrophils, mast cells, secretory IgA, proinflammatory cytokines, and nitric oxide, have been reported in Giardia -infected humans and mice [14,15,22,23,37-39]. A recent report described long-term CD4 + T cell proliferative responses in patients 5 years after acute giardiasis [40], suggesting unresolved immune activation during the post-clearance phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, the uptake of opsonised or unopsonised E. coli is the same in IL-4-treated and untreated macrophages, whereas Raveh et al (1998) showed an increase of the phagocytosis of Saccharomyces cerevisiae by thioglycollate elicited peritoneal macrophages after IL-4 treatment. Likewise, IL-4 stimulation of murine macrophages increased phagocytosis and killing of the parasite Trypanosoma cruzi (Wirth et al, 1989), but did not modify trophozoite uptake (Belosevic and Daniels, 1992). A recent paper indicated that the IL-4/STAT6 pathway limited the phagocytosis of small particles by the macrophages (Moreno et al, 2007).…”
Section: Effect On Endocytic and Phagocytic Pathway Referencesmentioning
confidence: 97%